Popularisierung im Dienst der Persuasion.: Beobachtungen zum öffentlichen Sprachgebrauch der Verwaltung zum Thema Migration - Carobbio, Gabriella (Linguistik Online, 2019)
The article outlines some strategies of persuasion when popularizing legal contents. The study concerns a video (Erklärfilm) published on the website of the Bayerisches Staatsministerium der Justiz, which explains to migrants the main legal principles upon which the German federal state is grounded. Legal issues such as the constitutional freedom of religion or belief and the state monopoly on the use of force are clarified in order to give migrants basic knowledge of the German legal system and, at the same time, to persuade them that it is reasonable and necessary to respect the law. The present investigation focuses on specific argumentation structures and different linguistic actions in order to highlight their contribution to the informative and persuasive purposes of the popularizing video. The linguistic analysis shall also point out some syntactic and lexical features used in knowledge transfer processes.